Uncovered interest rate parity and the expectations hypothesis of the term structure: Empirical results for the US and Europe - Ralf Brüggemann; Helmut Lütkepohl (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
A system of U.S. and euro area short- and long-term interest rates is analyzed. According to the expectations hypothesis of the term structure the interest rate spreads should be stationary and according to the uncovered interest rate parity the difference between the U.S. and euro area longterm interest rates should also be stationary. If all four interest rates are integrated of order one, one would expect to find three linearly independent cointegration relations in the system of four interest rate series. Combining German and European Monetary Union data to obtain the euro area interest rate series we find indeed the theoretically expected three cointegration relations, in contrast to previous studies based on different data sets.
Keywords: C32; 330; Expectations hypothesis of the term structure; uncovered interest rate parity; unit roots; cointegration analysis; Zinsparität; Zinsstruktur; Zinsstrukturtheorie; Kointegration; Unit Root Test; Schätzung; Europäische Wirtschafts- und Währungsunion; USA; EU-Staaten